Peningkatan Partisipasi Belajar Ipa Melalui Strategi Team Quiz Pada Siswa Kelas V Sd 3 Mejobo Kudus Tahun Ajaran 2015/2016 - Rizki, Annisa Insyirotun; , Dra Risminawati, M.Pd (2016)
Quality education is manifest by the presence of good character on each individual, education has a key role for the progress of the nation. But many of the facts are seen that education is primarily in elementary education are more likely to the teacher in the sense many students seen in passive learning, resulting in the low participation of student learning. This research aims (1) to improve participation learning science through strategy Team Quiz of class V SD 3 Mejobo Kudus year 2015/2016 and (2) to improve learning outcomes learning science through strategy Team Quiz on grade V SD 3 Mejobo Kudus year 2015/2016. This research is a research action class. The research was carried out during two cycles or four meetings. The subject of research that is the teacher of class V and grade V SD 3 Mejobo Kudus a number of 21 students. The technique of data collection conducted with observation, interviewing, documentation, and test. Technique of data analysis used namely data collection, reduction, rendering, and data verification. The results showed an increase in the participation of learning, namely: 1) at the stage of pre cycle amounted to 52%, 2) at this stage of the cycle I average being 4% 64.65) in cycle II increased to 78,25%. The conclusion of this study, namely the use of the Strategy Team Quiz can improve learning outcomes learning and participation in Natural Science subjects at grade V SD 3 Mejobo Kudus academic year 2015/2016.